Kewajiban Pejabat Pembuat Akta Tanah dalam Melaporkan adanya Transaksi Keuangan Mencurigakan Terkait Tindak Pidana Pencucian Uang oleh Klien - Rahmi, Zhafira Aulia; Sjafi’i, R. Imam Rahmat (Universitas Negeri Malang, 2019)
This study seeks to analyze the problemation in regards to the duty of official land deed (PPAT) on reporting the suspicious of financial transactions that related to money laundering by the client, related to conflict of norm that an official land deed should be conceal the transactions of client instead of reporting client if there’s a suspicious financial transaction but the government told them to report. This study is questioning in regards to the meaning and criteria the duty of official land deed on reporting the suspicious financial transactions related to money laundering by the client. The type of this research is a normative with statue, conceptual, and historical approach. The conclusions of this study that there are conflict of norm that the land deed’s duty can be solved by using Lex Posterior Derogat Legi Priori principle.